Volatilitas Abnormal Saham BEI Pasca-Rebalancing MSCI - Siti Shoimatul Azizah; Sholehatul Inayah; Kholifatan Nisa (CV. SINAR HOWUHOWU, 2026)
The quarterly MSCI index rebalancing triggered massive foreign flows to the IDX (US247 million per inclusion event) as global ETFs were required to adjust their portfolios. The IDX's low free float (25%) and reliance on foreign flows for 40% of daily transactions created extreme volatility. The trading halt in March 2025 (-5%, post-rebalancing) and the MSCI freeze on January 27, 2026 (JCI -8%, trading halt at 1:43 PM WIB) are evidence of a systemic phenomenon. The objectives of this study are: (1) To measure the impact of MSCI rebalancing on stock volatility; (2) To identify the differences between inclusion and exclusion; (3) To identify the determinants of volatility. The research method used an integrated GARCH(1,1) event study on 40 LQ45/IDX30 stocks from 20 rebalancing events from 2020-2025 (February, May, August, and November). Secondary data was used from Yahoo Finance's daily prices, official MSCI announcements, and IDX foreign flow. Estimation window (-120/-21 days), event window (-10/+20 days), paired t-test, fixed effects panel regression. The MSCI announcement caused stock volatility to increase 46% (from 1.45% to 2.12% daily) due to simultaneous buying/selling by foreign ETFs. Stocks included in the index (such as BREN +244%, BBRI inflow 320 million) were more volatile than stocks excluded (KLBF -5.3% panic selling). GARCH shows the effect persisted for 20+ days—not just 1-2 days. Panel regression evidence shows that volume increased 42% (β=0.58), and the weak rupiah (β=0.33) exacerbated the volatility, while large-cap stocks (BBCA) were more stable (β=-0.24).